A Comparative Study on Financial Performance of Selected Public (Indian Bank) and Private (Hdfc Bank) Sector Banks in India - M. SUBRAMANYIAM REDDY, Dr. N. RAJENDHIRAN (International Journal of Advanced Science and Technology, 2020)
In India, The public sector together with private sector banks are very significant role in economicdevelopment in India. Usually, banks has involved in accepting deposits from the people (public) at alower rate and issuing loans at higher rate and thereby making profit on interest margin. This paperaimed to analyze and differentiate the financial performance of selected public and private sector banksin India during from 2015 to 2019. The study period covers the five years of selected public (i.e. IndianBank) along with private (i.e. HDFC Bank) sector banks. The study based on secondary source of datacollected from their official sites and annual reports and the data analyzing through financial ratio andstatistical tools such as Mean, Standard Deviation, Co- efficient of variance and F-Test (ANOVA) withhelp of SPSS. We analyzed the financial strength and weakness of the selected public along with privatesector banks. In this paper, we ascertain that the private sector banks are best utilization of the accessibleresources such as deposits, advances, assets, along with investments and it was also practical in the studythat public sector banks have not utilized of their available resources properly. Therefore it has neededfor the public sector banks to play more awareness on improving their efficiency and productivity ofemployee training, incentive and proper management